Commission shops as providers of basic household goods : the case studies of Slovenia and Czechoslovakia - Habinc, Mateja (Array, 2019)
Mostly through the case studies of the Slovenian Komisija and Czechoslovak Chronor, Klenoty and Bazar stores, this article presents socialist commission shops as providers of basic household goods. It therefore contributes insights into the complexity of commission shops as a specific type of second-hand retail as well as insights into the complexity of types of retail and socialist consumerism in general. It briefly compares commission shops with some other socio-historically known forms of second-hand retail, while pointing to the differences and similarities among them.